The Effectiveness of Da'wah In Promoting a Boycott of Pro-Israel Products: Challenges and Opportunities for Local Economic Growth - Iim, Ade (Studi Multidisipliner: Jurnal Kajian Keislaman, 2024)
This research aims to determine the effectiveness of da'wah in mobilizing a boycott of Israeli products, which some people ignore and even confirm that they are used explicitly or implicitly. The research method used is a qualitative descriptive method by looking holistically at the opportunities and growth of the local economy if there is a boycott of Israeli products. The focus of this research is the effectiveness of da'wah in encouraging boycotts of pro-Israel products. It was found that the internalization of religion is always influenced by the individual himself. This is what causes Islamic culture to be easily accepted among society because Islam can acculturate with the customs, beliefs, and culture that develop within society itself without any ambition to disappear that culture. has existed. existed before. Apart from that, the process of spreading Islam through cultural channels, Islamic preachers tended to be subtle in conveying religious teachings to a society that was considered heterogeneous in terms of its cultural values. So the effectiveness of boycotting Israeli products will not be a significant challenge because local economic growth will continue to grow and remain at market balance.